The Impact of Dividend Policy, Capital Structure, and Earning Growth on Firm Value: Study on the Pharmacy Sub-Sector Listed on the IDX 2010-2024 - Ayuning Rizqi Rahmayanti; Mahatma Kufepaksi; Nindytia Puspitasari Dalimunthe (LPPPIPublishing, 2026)
This research analyzes how dividend policy, capital structure, and earnings growth influence firm value in pharmaceutical sub-sector companies listed on the Indonesia Stock Exchange over the 2010–2024 period. Firm value is represented by Price to Book Value (PBV), dividend policy is proxied by the Dividend Payout Ratio (DPR), capital structure is measured using the Debt-to-Equity Ratio (DER), and earnings growth is calculated through the growth rate of Earnings Per Share (EPS). Firm size, expressed as the natural logarithm of total assets, is incorporated as a control variable to account for differences in company scale. The study applies purposive sampling and includes 105 firm-year observations derived from seven selected companies. The analysis utilizes descriptive statistics, classical assumption testing, multiple linear regression, and hypothesis evaluation through partial and simultaneous significance tests. The findings reveal that dividend policy has a negative and statistically significant relationship with firm value, indicating that greater dividend distributions tend to correspond with lower market valuation. Conversely, capital structure and earnings growth do not show significant effects on firm value during the observation period. These results suggest that investors in the pharmaceutical industry may place greater emphasis on broader performance and strategic factors rather than leverage composition or short-term profit growth alone. Additionally, firm size demonstrates a significant association with firm value, highlighting the relevance of corporate scale in shaping market appraisal. This study contributes empirical evidence to support financial decision-making and investment analysis in the pharmaceutical sector.